2022
DOI: 10.3390/ijerph192013222
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Smoking Cessation on Body Weight and Other Metabolic Parameters with Focus on People with Type 2 Diabetes Mellitus

Abstract: Smokers with diabetes mellitus substantially lower their risks of microvascular and macrovascular diabetic complications, in particular cardiovascular disease, by quitting smoking. However, subsequent post-smoking-cessation weight gain may attenuate some of the beneficial effects of smoking cessation and discourage attempts to quit. Weight gain can temporarily exacerbate diabetes and deteriorate glycemic control and metabolic profile. The molecular mechanisms by which quitting smoking leads to weight gain are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 23 publications
(8 citation statements)
references
References 166 publications
1
7
0
Order By: Relevance
“…In our study, we confirmed their significant impact on weight reduction, with an additive effect. Both nicotine and caffeine were found to suppress food intake, supporting previous studies (33,34) . However, apart from normal mice, there were no significant differences in food intake among the groups, suggesting that weight change is unrelated to food intake.…”
Section: Discussionsupporting
confidence: 89%
“…In our study, we confirmed their significant impact on weight reduction, with an additive effect. Both nicotine and caffeine were found to suppress food intake, supporting previous studies (33,34) . However, apart from normal mice, there were no significant differences in food intake among the groups, suggesting that weight change is unrelated to food intake.…”
Section: Discussionsupporting
confidence: 89%
“…The Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) reporting guidelines [ 12 ] were adhered to in this systematic review. The PECO (Population, Exposure, Comparator, Outcome) protocol for the systematic review was defined as follows.…”
Section: Reviewmentioning
confidence: 99%
“…As smoking cessation leads to weight gain, this could be an interesting approach for patients with significant weight loss that should not be eliminated right away [47 ▪ ]; it may prevent surgical complications and also may decrease the risk of second cancers, which is still a significant problem in disease-free patients with PDACs [5 ▪ ].…”
Section: Correcting Known Risk Factors and Prehabilitation Programsmentioning
confidence: 99%